Welfare and Poverty Impacts of Cocoa Price Policy Reform in Cote d'Ivoire - Katayama, Roy; Dabalen, Andrew; Nssah, Essama; Amouzou Agbe, Guy Morel (World Bank, Washington, DC, 2018)
Cote d'Ivoire is the world’s leading cocoa producer, supplying nearly 40 percent of world cocoa production. Developments in the cocoa sector can have significant implications for poverty reduction and shared prosperity given that the sector is a source of livelihood for about one-fifth of the population, as well as an important source of export and government revenues. Cocoa pricing has always been a major focus of public policy in the country, and in 2011 the government initiated a new round of cocoa sector reforms seeking to stimulate cocoa production and to secure the livelihoods of cocoa farmers through guaranteed minimum farm-gate prices. Policymakers will certainly like to know the likely impacts of this price policy reform on household welfare and poverty. This paper uses a nonparametric approach to policy incidence analysis to estimate the first-order effects of this policy reform. To assess the pro-poorness of the reform in cocoa pricing, variations in poverty induced by the policy are compared to a benchmark case. While increasing the cocoa farm-gate price has a potential to reduce poverty among cocoa farmers, it turns out that the increase in 2015-2016 translates into a relatively small drop in overall poverty. This variation is assessed to be weakly pro-poor. It is likely that this poverty impact can be amplified by additional policy interventions designed to address the key constraints facing the rural economy such as productivity constraints stemming from factors such as lack of relevant research and development, weak extension services, poor transportation and storage infrastructure, and generally poor provision of relevant public goods. Addressing these issues require a coherent policy framework that can be effectively implemented by accountable institutions to increase the role of agriculture as an engine of inclusive growth in Cote d'Ivoire.